IMPLEMENTASI GERAKAN LITERASI SEKOLAH DITINJAU DARI TAHAP PENGEMBANGAN DI SD MUHAMMADIYAH - Putri, Ragil Dian Purnama; Maryani, Ika (Universitas Pendidikan Indonesia, 2021)
This study aims to determine the activities of the development phase of GLS in SD Muhammadiyah Sumbermulyo and its supporting and inhibiting factors. This type of research uses a descriptive qualitative approach. The subjects of the research are the school principal, class I, IV, and V teachers, librarians and class I, IV, and V. Students while the objects are all things related to the development phase of GLS in SD Muhammadiyah Sumbermulyo. Data collection techniques used include observation, interviews, and documentation. In testing the validity of the data using source triangulation and technique triangulation. The results showed that the implementation of the GLS program had been carried out since 3 years. The literacy program of the development phase includes the activities of the Qur'an, 15-minute reading activities, the literacy activities of the development stage, the use of libraries and reading angles, and the selection of literacy children. Supporting factors are school community awareness of the importance of literacy activities, adherence to GLS guidelines from the government and the Republic of Indonesia Minister of Education's Regulation No. 23 of 2015 on the Development of Characteristics, literacy activities held by schools, collaboration of school libraries with other libraries, and parents' support. The inhibiting factors are discipline in literacy that has not been implemented by all students, some teachers are not maximized in literacy culture, low student interest in literacy activities, and lack of time for literacy activities in low classes.